Investigating admixture and selection in gyrfalcon (Falco rusticolus), saker falcon (Falco cherrug) and their hybrids using comparative whole-genome sequencing analysis - FAROOQ OMAR MAAN AL-AJLI (11557168) (2021)
Gyrfalcon (Falco rusticolus) and saker falcon (Falco cherrug) are closely related species and iconic avian apex predators that play crucial ecological roles in their habitats across Eurasia and North America. Both species are threatened and require focused conservation and management programs. This thesis presents a genome-scale approach to understand speciation, hybridisation, adaptation, population structure, phylogeny, and demographic history by producing chromosome-level reference-quality genome assembly for the gyrfalcon, and analyses the genetic differentiation of multiple falcon populations. The results presented in this thesis will aid the conservation efforts of these two birds.